Tenosynovitis of the extensors and abductor of the thumb. Review of 2 cases and results of the application of the transverse massage prof undo - Martin Urrialde, J A (Cuestiones de Fisioterapia, 1999)
62 patients were treated by Cyriax techniques, and a revision of results, shown the great valueand easy aplication of MTR